Sanctifying Ethnic Memory and Reinforcing Place Attachment: Cultural Identity, Sacred Place, and Pilgrimage in Esterhazy, Saskatchewan - Kovacs, Jason (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
On November 8,1908, the Our Lady of Assumption Church was opened in the Hungarian Catholic community of Kaposvar, Saskatchewan (located 4 km south of the present-day town of Esterhazy). Nearly a century later, the focal point of the early farming district remains an important commemorative site in eastern Saskatchewan for descendants of the pioneers who settled in the Kaposvar district under Count Paul d'Esterhazy's 1886 Hungarian colonization initiative. Centred on the church grounds, commemorative celebration and an annual pilgrimage have served as important agencies of cultural retention for local Hungarian-Canadians. This paper explores the evolution of cultural identity in the former ethnic enclave of Kaposvar and reveals the role of a traditional religious pilgrimage in reinforcing identity forming place attachment.